Emergency laparoscopic ileocecal resection for a low-grade appendiceal mucinous neoplasm with impending rupture: A case report. (March 2021) - Kitagawa, Yusuke; Hamasaki, Shunsuke; Harada, Toshiko; Tamura, Noriyasu; Katsuno, Akira; Umetani, Naoyuki
Highlights: Appendiceal mucinous neoplasms account for less than 1% of all cancers. LAMNs have an aggressive biological potential. Preoperative diagnosis of appendiceal mucinous neoplasms is difficult. Here, we used emergency MRI to identify nodules in the appendix before operation. Abstract: Introduction and importance: We report the case of a patient with a low-grade appendiceal mucinous neoplasm (LAMN) who underwent emergency laparoscopic ileocecal resection to avoid the metastatic spread of tumor cells due to an impending rupture. Case presentation: A 55-year-old woman presented to our hospital with pain in the right lower quadrant of the abdomen. Computed tomography revealed a markedly tense appendiceal mucinous tumor with surrounding inflammation, and laboratory test results showed elevated serum C-reactive protein (7.47 mg/dL), indicating impending rupture of the appendix. Magnetic resonance imaging revealed nodules inside the appendix, suggesting the possibility of appendiceal cancer. We performed emergency laparoscopic ileocecal resection with regional lymph node dissection. The tumor was pathologically diagnosed as a LAMN without rupture. Clinical discussion: LAMN is classified as a clinically malignant tumor because it can cause pseudomyxoma peritonei due to perforation or the presence of residual tissue. Although an appendectomy would be appropriate for LAMN if the tumor margin is secured, ileocecal resection with lymph node dissection is necessary when preoperative discrimination of appendiceal cancer is impossible. Conclusion: Further studies of preoperative imaging for appropriate differential diagnosis were necessary.